Introduction to the art of Anne and Patrick Poirier. Ideas and works from Villa Medici to Villa Adriana (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
Anne and Patrick Poirier’s artistic research, particularly on the theme of memory, has been nourished by the ancient ruins that they had the occasion to study during several trips. A major influence came to them from Villa Medici and from Hadrian’s Villa, which they repeatedly visited in 1977.
Keywords: Anne Poirier; Patrick Poirier; Villa Medici; Domus Aurea; Villa Adriana; Venice Biennale; garden of memory; contemporary necropolis; memory; art; photography; architecture; archaeology